2018
DOI: 10.1016/j.omtn.2018.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Strategies for HIV Treatment and Prevention

Abstract: Conventional HIV gene therapy approaches are based on engineering HIV target cells that are non-permissive to viral replication. However, expansion of gene-modified HIV target cells has been limited in patients. Alternative genetic strategies focus on generating gene-modified producer cells that secrete antiviral proteins (AVPs). The secreted AVPs interfere with HIV entry, and, therefore, they extend the protection against infection to unmodified HIV target cells. Since any cell type can potentially secrete AV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 203 publications
(237 reference statements)
0
14
0
1
Order By: Relevance
“…A promising prevention plan, which has been used in a clinical trial, utilizes the cell that is capable of secreting antiviral proteins (AVPs). AVPs have the capability to defend HIV target cells that have not been previously altered [15]. These findings are hopeful because both hematopoietic and non-hematopoietic cells can release AVPs allowing for all cell types to be reached [15].…”
Section: Aids Therapy and Treatmentsmentioning
confidence: 98%
See 1 more Smart Citation
“…A promising prevention plan, which has been used in a clinical trial, utilizes the cell that is capable of secreting antiviral proteins (AVPs). AVPs have the capability to defend HIV target cells that have not been previously altered [15]. These findings are hopeful because both hematopoietic and non-hematopoietic cells can release AVPs allowing for all cell types to be reached [15].…”
Section: Aids Therapy and Treatmentsmentioning
confidence: 98%
“…AVPs have the capability to defend HIV target cells that have not been previously altered [15]. These findings are hopeful because both hematopoietic and non-hematopoietic cells can release AVPs allowing for all cell types to be reached [15]. A potential treatment for HIV also involves the use of hematopoietic cells, specifically RNA-based hematopoietic cells [16].…”
Section: Aids Therapy and Treatmentsmentioning
confidence: 99%
“…Gene therapy holds considerable promise for functional cure of HIV infection, and in this context, genetically engineered HIV-resistant cells represent a powerful strategy which has been proven by the cure of the "Berlin patient" and the "London patient"; these two patients were transplanted with allogeneic hematopoietic stem cells (HSCs) harboring a naturally occurring CCR5Δ32 mutation (3,4). However, such a procedure is not easy to duplicate and thus is not practical for the treatment of a larger population; instead, disruption of CCR5 by gene editing has been extensively explored (5)(6)(7). While CCR5 editing confers resistance to CCR5-tropic (R5) viruses, this strategy would be ineffective for CXCR4-tropic (X4) and dual-tropic (R5X4) viruses.…”
mentioning
confidence: 99%
“…A phase I clinical trial showed that infusion of maC46-modified autologous T cells into HIV-infected patients with advanced disease and HAART failure was well tolerated, with a significant increase of CD4 counts (25). Moreover, maC46 has been explored for combination gene therapy with a short hairpin RNA (shRNA) or a high-affinity P2-CCL5 intrakine to CCR5 (6,(26)(27)(28)(29)(30). Compared to T20, the CHR-derived peptide C34 has more potent anti-HIV activity, and thus, it has been widely used as a template to develop new HIV-1 fusion inhibitors (31).…”
mentioning
confidence: 99%
“…Anticorps monoclonaux : quand les cellules de l'immunité s'en mêlent musculaires avec des vecteurs viraux, lentivirus et virus adéno-associé, codant un anticorps neutralisant le VIH-1[5]. Une approche ex vivo consisterait, quant à elle, à isoler des cellules souches hématopoïétiques et à les transduire avec un vecteur lentiviral codant le bNAb avant de les réimplanter in vivo[6].…”
unclassified